Characterization of silver nanoparticle-infused tissue adhesive for ophthalmic use. (March 2016) - Yee, William; Selvaduray, Guna; Hawkins, Benjamin
Abstract: In this work, we demonstrate the successful enhancement of breaking strength, adhesive strength, and antibacterial efficacy of ophthalmic tissue adhesive (2-octyl cyanoacrylate) by doping with silver nanoparticles, and investigate the effects of nanoparticle size and concentration. Recent work has shown that silver nanoparticles are a viable antibacterial additive to many compounds, but their efficacy in tissue adhesives was heretofore untested. Our results indicate that doping the adhesive with silver nanoparticles reduced bacterial growth by an order of magnitude or more; nanoparticle size and concentration had minimal influence in the range tested. Tensile breaking strength of polymerized adhesive samples and adhesive strength between a T-shaped support and excised porcine sclera were measured using a universal testing machine according to ASTM (formerly American Society for Testing and Materials) standard techniques. Both tests showed significant improvement with the addition of silver nanoparticles. The enhanced mechanical strength and antibacterial efficacy of the doped adhesive supports the use of tissue adhesives as a viable supplement or alternative to sutures. Graphical abstract: Highlights: FDA-approved tissue adhesive was doped with silver nanoparticles. Different nanoparticle sizes and concentrations tested using standard (ASTM) methods. Antibacterial efficacy and mechanical strength improved with nanoparticle addition.